Detection of the Thermolabile hemolysin (tlh) and thermostable drect hemolysin (tdh) gene of Vibrio parahaemolyticus by PCR - Uyen, Nguyen Hoang; Thuan, Nguyen Chi; Thanh Loi, Nguyen Thi; Hong Hanh, Nguyen Thi (Academia Journal of Biology, 2015)
Vibrio parahaemolyticus is a halophytic bacterium found in black tiger shrimp culture ponds and is associated with shrimp diseases. All V. parahaemolyticus strains carry the thermolablile hemolysin (tlh) that appears to be species specificgene. The production of the thermostabile direct hemolysin (tdh) by V. parahaemolyticus is associated pathogenically qith the organism and is encoded by the tdh gene. The V. parahaemolyticus biochemical indentication method requires 5-8 days and did not detect the pathogen strains. The PCR and multiplex PCR methods which amplify tlh and tdh genes are used to detect various strains of V. parahaemolyticus. All 7 isolated V. parahaemolyticus strains are controlledby the API 20E showed and by PCR method, show the presemee of the tlh gene, however only two strains VpPM4 and ATCC17803 carry the tdh gene. The multiplex PCR method is also and successfully to detect these two strains VpPM4 and ATCC17803.